The ethics and social mission of workers and their relationship to social intrapreneurship. - Galván Vela, Esthela; Mercader-Pomarón, Victor Manuel; Ravina-Ripoll, Rafael (My University, 2023)
Intrapreneurship (i.e., entrepreneurship arising within established organizations) is key to the development of the entities that generate it. This is why highly positive results have been attributed to it. This construct has been analyzed for more than three decades; however, social intra-entrepreneurship, which arises from the need of companies to be recognized as entities that generate social value from their mission, still lacks sufficient scientific background. Therefore, for the first time, this study empirically evaluates social mission and business ethics as determinants of social intrapreneurship. A questionnaire was used to gather data from 603 professionals from different Baja, California, and Mexico companies. Among the data analysis techniques, descriptive statistics were used to verify the univariate composition of the data, and inferential statistics were used to determine the reliability and validity of the measurement scales. The data indicate a highly significant relationship between corporate social mission and social intrapreneurship; however, the data indicate that business ethics is not related to acts of social intrapreneurship.
La ética y la misión social de los trabajadores y su relación con el intraemprendimiento social.
Anduli Revista Andaluza de Ciencias Sociales
Keywords: Ethics; Social intrapreneurship; Social mission; Business; Human capital; Campus Tijuana